2010
DOI: 10.1073/pnas.0913353107
|View full text |Cite
|
Sign up to set email alerts
|

Formation of nitrogenated organic aerosols in the Titan upper atmosphere

Abstract: Many aspects of the nitrogen fixation process by photochemistry in the Titan atmosphere are not fully understood. The recent Cassini mission revealed organic aerosol formation in the upper atmosphere of Titan. It is not clear, however, how much and by what mechanism nitrogen is incorporated in Titan's organic aerosols. Using tunable synchrotron radiation at the Advanced Light Source, we demonstrate the first evidence of nitrogenated organic aerosol production by extreme ultraviolet-vacuum ultraviolet irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
107
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 37 publications
3
107
0
Order By: Relevance
“…The model behavior is again consistent with the observations. Therefore, the simultaneous reproduction of multiple Cassini observations by our simulation provides strong evidence for the production and growth of aerosol particles in Titan's ionosphere and supports previous theoretical and laboratory studies suggesting that the aerosol is produced in the upper atmosphere (11,13,14,(35)(36)(37)(38).…”
Section: Lessons From Titansupporting
confidence: 67%
“…The model behavior is again consistent with the observations. Therefore, the simultaneous reproduction of multiple Cassini observations by our simulation provides strong evidence for the production and growth of aerosol particles in Titan's ionosphere and supports previous theoretical and laboratory studies suggesting that the aerosol is produced in the upper atmosphere (11,13,14,(35)(36)(37)(38).…”
Section: Lessons From Titansupporting
confidence: 67%
“…Specifically, estimated N/C and O/C ratios were obtained by fitting the full CNO spectra with atomic absorption coefficients (Henke et al 1993) using the model described in Cody et al (2008). Imanaka and Smith (2010) previously determined a N/C ratio of 0.93 for the poly-HCN sample using combustion elemental analysis. This is consistent with the XANES determination of a N/C ratio of ∼0.9.…”
Section: Xanes Spectroscopymentioning
confidence: 99%
“…This paper focuses on the properties of the refractory residues that result from these irradiation experiments using multiple analytical techniques, including FTIR spectroscopy (mid-and near-IR regions, from 7000 to 600 cm −1 , 1.43-16.7 μm), X-ray absorption near-edge structure (XANES) spectroscopy, and gas chromatography coupled with mass spectroscopy (GC-MS). The properties of the residues from the UV-and e − -irradiated ices are also compared to samples of poly-HCN provided by Bob Minard (Minard et al 1998) and later analyzed by Hiroshi Imanaka (Imanaka & Smith 2010). Poly-HCN has been suggested as a possible component of the refractory carbonaceous material found on comets and on the surfaces of objects in the outer Solar System (e.g., Cruikshank et al 1991;Matthews 1992) and has been previously compared to Titan-like tholins produced in the laboratory (Vuitton et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Later, Vinogradoff et al (2012) confirmed the importance of methanimine in the formation of 1,3,5-triazinane (an intermediate species toward hexahydro-1,3,5-triazine formation) and polymethylenimine in non-UV exposed NH 2 CH 2 OH:HCOOH ice mixtures between 290 and 330 K. Vuitton et al (2007) suggested that a similar process could account for the missing quantitative loss process in the atmosphere of Titan, while Lavvas et al (2008a,b) went further by suggesting that polymerization of methanimine could be an important step in the formation of the haze aerosols in the Titan upper atmosphere. Indeed, there is overwhelming evidence that the aerosols, which form the haze of Titan, are composed of organic macromolecules that are very rich in nitrogen (Israel et al 2015;Imanaka & Smith 2010;Gu et al 2009;Carrasco et al 2009;Cable et al 2012). Therefore, CH 2 =NH is an excellent monomer candidate to account for the nitrogen-rich aerosols of Titan through polymerization.…”
Section: Introductionmentioning
confidence: 99%